Analisis selisih biaya pembangunan proyek kontruksi pada pt tastia permata sejahtera di samarinda - Donny Rozano (Faculty of Economics and Business Mulawarman University, 2016)
The problems of this study was to determine whether the actual cost of the constructions projects in the Mosque Nurul Ilmi Loa Bakung experiencing favorable or unfavorable difference. The purpose of this research is to determined the magnitude of the differnce between the budget and actual costs in the execution of the project to determine the factors that cause the difference between budget and realization. The data used is the budget cost of raw materials, direct labor costs and factory overhead costs and realization costs of raw material costs, direct labor costs and factory overhead costs for the construction of Mosque Nurul Ilmi. From the research, the costs incurred difference is the cost of materials amounting Rp.44,810,000.00 excess quantity of raw materials Rp.15,450,000.00 and factory overhead cost difference of Rp.103,180,000.00. From these results between budget and realization of Rp.163,440,000.00.Keyword: Variance Analysis, Cost of Production, Raw Material Costs, Overhead Cost